FOOD BORNE PARASITIC ZOONOSIS WITH SPECIAL REFERENCE TO METACERCARIAL INFECTION IN FISHES - S. Marcus; A. Maqbool; N. Khan; K. J. Iqbal; K. Ashraf; N. Ahmad (Journal of Animal and Plant Sciences, 2012)
The study was conducted to evaluate the prevalence of food borne trematode infections in commercially important fish species of Pakistan such as, Labeo rohita (rohu), Cirrhinus mrigala (mori), Catla catla (thaila), Hypophthalmichthys molitrix (silver carp). For this purpose 222 different samples of fishes were collected from different water bodies i.e. Rawal Dam, Islamabad, Mangla Dam (Mirpur) and local fish markets, Lahore. The detection of infectious metacercariae of Opisthorchis, Clonorchi and Heterophyid were done by pepsin digestion technique. Overall infection rate was recorded as 28.37%. Species wise prevalence indicated that Catla catla and Labeo rohita were more frequently affected, whereas the lowest (23.5%) prevalence was reported in Hypophthalmichthys molitrix.
Keywords: Indian major carps; Trematode; Prevalence; Intensity